P27 Deprivation in the copd salford lung study (sls) is associated with higher healthcare costs but does not moderate the main outcomes. (15th November 2017) - Jones, R; Nicholls, A; Browning, D; Bakerly, N Diar; Woodcock, A; Vestbo, J; Leather, D
Abstract : Introduction and Objectives: The SLS was a pragmatic randomised controlled trial (RCT) of initiating fluticasone furoate/vilanterol (FF/VI) versus continuing usual care (UC) and aimed to recruit a real life population in a near normal care setting. The 12 month study required only two patient visits and most data was collected using electronic health records. This post-hoc sub-study assesses the impact of deprivation on health behaviours, healthcare costs and main/safety outcomes. Methods: Deprivation scores were derived by postcode using the countrywide indices of deprivation (version 2010). The indices were categorised into quintiles. The primary effectiveness endpoint of mean annual rate of moderate or severe exacerbations, and primary and secondary care contacts were re-analysed using the same generalised linear models as for the original SLS study but with the addition of a treatment by deprivation quintile interaction term. Results: Participants in the more deprived categories were more likely to be younger, more likely to smoke and slightly more obese but were balanced between genders. There was no association with deprivation and withdrawal rates or with adherence (proportion of days covered). An additional post-hoc analysis demonstrated that Deprivation was associated with more primary and secondary care contacts and higher costs (Table). Deprivation did not interact with the effect of FF/VI v UC on the primary outcome measure (annual rate of moderate to severe exacerbations) or health care contacts or safety endpoints including all-cause mortality and pneumonia. Conclusions: The unique design of SLS allowed the RCT to be conducted in a deprived population who would normally be excluded from RCTs. Higher deprivation was not associated with higher drop-out rates or poor adherence, but was associated with higher rates of smoking, obesity and co-morbidities and higher health care consumption and costs. With its once daily dosage and ease of use FF/VI had potential to benefit people with poor adherence and preferentially benefit deprived populations, however deprivation scores did not moderate the effect of FF/VI v UC in primary, secondary or safety outcomes. Funding: GSK (HZC115151/NCT01551758 ). Please refer to page A258 for declarations of interest in relation to abstract P27.